(3HOGFY GdHOGFIs - (3Ydj Hf XGaQ Hf MSjf GdCROj GdNRQLj, CHh GdMSf LeGd GdOjf,J (B613 (3g` s ((3YHO Gddg Hf YHO Gddg Hf SdGeI GdeDPf GdEOcGhi s)
(3ChdgG (B:s
(3hHYO abO cfJ ai UOQ YeQi fTWJ dLeY CNHGQ GdTYQGA ai GdHOGFI hGdGQJLGd hLeYJ efgG McGjGJ de jQbegG ai GdWQS HfGJ , hde jWeKgG bHdi EfS hdGLGf, aGhbaJ YdjgG s
(3BNQgG (B:s
(3CheeG JLOO ai GdCRefI GdBJjI LeYJg , hLYdJg cGdSeI dg , MJi dG CaV NJGei hdG Cajb ceGeg , hGddg JYGdi jhbYg YfO GdLfGH GdYGdi GdeMehd Edjg , ehbY GdQVG hGdEbHGd Ydjg Ef TGA Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3Ydi gGeT HYV GdJUMjMGJs
(3fSNI KGfjIs
(3JNJda ebOeJgG Yf ebOeI GdfSNI GdChdi hjHOh CfgG UfYI KGfjI ddeDda s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdCOHs